Contemporary international law before de rules-based international order - Maúrtua de Romaña, Oscar (2025)
This article analyzes the evolution and challenges faced by the Rules-Based International Order (RBI) in its relationship with Contemporary International Law (DIC), highlighting the need to strengthen both approaches to face current global challenges. The main objective is to examine how the OIBR – which emerged after World War II and is based on rules, treaties and institutions – seeks to promote peace, cooperation and stability among states, even if it faces criticism of instrumentalization by certain hegemonic powers, especially Western ones. Using a historical and legal analysis, the main mechanisms that cemented the OIBR will be reviewed, as well as a review of the current international context, marked by the Russian-Ukrainian conflict and the crisis in Gaza, where the tension between the OIBR and the DIC is evident. It is concluded that, although both systems share fundamentals, the OIBR can be used selectively, which weakens its legitimacy. Therefore, it is proposed to reformulate the notion of state sovereignty and strengthen multilateralism to adapt to a multipolar world and face global challenges such as climate change, artificial intelligence, transnational crime, among others.